The System of Political Economy of China - Elya Novita Sari Situmorang (International Journal on Social Science, Economics and Art, 2021)
This research tried to explain about the transition of China’s economic system from a socialist to capitalist system. This research was aimed at describing the factors that influence the transition of China’s economic system from a socialist to capitalist system in the perspective of comparative analysis. Therefore, the political interaction is related to the leadership of Mao Zedong as China’s revolutionary leader to socialism and the leadership of Deng Xiaoping who reformed China to capitalist system. This research also described condition of the people of China under capitalist system. This research used datas that come from books, archieves, documents, and websites. The method analysis that is used for this research was the descriptive qualitative method which is done by making, describing, summarizing from many conditions with some variables appeared on the object of this research, and revealing facts by gathering datas to be learned, processed, analyzed, and interpreted descriptively. The writer used the theory of Political Economy Theory and Marxism Socialism Theory. The Theory of Political Economy is used for describing and analyzing the China’s economic system under Mao Zedong and Deng Xiaoping. Meanwhile, Marxism Socialism Theory is used for reviewing China’s political economic as socialist country in the perspective of Marx. Hence, the writer is able to conclude the internal and external factors that influence the transition of China’s economic system. The Internal factor was caused by the high levelof inequality between the people of China as a result of the first phase of the transition from a feudalist system to socialist system that still left the bourgeoisie character in China. Consequently, the bourgeoisie character still left in the leadership of China’s Communist Party. This created the different views for marxist and revisionist group that looked upon the contradictions of the people of China. While the external factor was caused by the defeat of Uni Soviet as the central of socialist country and the black campaign by the world countries for viewing socialism under Mao zedong.